OPPORTUNITIES FOR TEACHING FOREIGN LANGUAGES IN UZBEKISTAN (The Role of Exact Sciences in the Era of Modern Development, 2023)
This article is aimed at encouraging the attention of today's youth to study foreign languages, spend their time productively, and respond appropriately to the opportunities provided by our country.